Desert dermatoses (Thar desert, India) - Manas Chatterjee (Wolters Kluwer Medknow Publications, 2017)
Desert dermatology describes the cutaneous changes and the diseases affecting those living in the desert. Diurnal variation in temperature is high and is characteristic of the deserts. The lack of water affects daily activities and impacts dermatological conditions. Adaptation to the desert is, therefore, important to survival. Infections are the most common conditions seen among this population, and among them, fungal infections are the most common. The high incidence of these infections would be accounted for by the poor hygienic conditions due to lack of bathing facilities due to scarcity of water and the consequent sweat retention and overgrowth of cutaneous infective organisms. Pigmentary disorders, photodermatoses, leishmaniasis, and skin tumors are found to be more prevalent in this region. Desert sweat dermatitis was another specific condition found to have an increased incidence. The environment of the desert provides for a wide variety of dermatoses that can result in these regions with few of these dermatoses found in much higher incidence than in other regions.